Vegetative Propagation Methods of Leonurus Cardiaca L. and L. Turkestanicus V.I. Krecz. & Kuprian - qizi, Bahodirova Gavharkhon Ikrom; Xusanboyevich, Maxkamov Trobjon; Abdijabborovich, Raxmatov Abdurashid; qizi, Qurbonova Sarvinoz Anvar (American Journal of Biology and Natural Sciences, 2025)
The botanical description, systematics, distribution range, bioecology, introduction, ontogenesis, phenology, phytochemistry, applications, methods of using raw materials, pharmacological effects, cultivation agrotechnology, and productivity of species of the genus Leonurus (motherwort) are widely reported in the scientific works of many researchers around the world. Sufficient information is also available on the generative propagation of Leonurus species by seeds. However, there is a lack of scientific studies on the vegetative propagation of these species. This article presents the results of research on the propagation of common and turkestan motherwort by dividing the clump and by rhizomes.